Comparison of BISAP, Ranson, MCTSI, and APACHE II in Predicting Severity and Prognoses of Hyperlipidemic Acute Pancreatitis in Chinese Patients - Lixin Yang; Jing Liu; Yun Xing; Lichuan Du; Jing Chen; Xin Liu; Jianyu Hao (Gastroenterology Research and Practice)
In recent years, with the developing of living standard, hyperlipidemia becomes the second major reason of acute pancreatitis. It is important to predict the severity and prognosis at early stage of hyperlipidemic acute pancreatitis (HLAP). We compared the BISAP, Ranson, MCTSI, and APACHE II scoring system in predicting MSAP and SAP, local complications, and mortality of HLAP. A total of 326 diagnosed hyperlipidemic acute pancreatitis patients from August 2006 to July 2015 were studied retrospectively. Our result showed that all four scoring systems can be used to predict the severity, local complications, and mortality of HLAP. Ranson did not have significant advantage in predicting severity and prognosis of HLAP compared to other three scoring systems. APACHE II was the best in predicting severity of HLAP, but it had shortcoming in predicting local complications. MCTSI had outstanding performance in predicting local complications, but it was poor in predicting severity and mortality. BISAP score had high accuracy in assessment of severity, local complications, and mortality of HLAP, but the accuracy still needs to be improved in the future.